(untitled) (Fractal: Journal of Psychology, 2009)
Throughout the history of psychoanalysis, the freudian postulate of the phallus primacy in the construction of sexuality has resulted in a controversy about its role in femininity. In order to retrace this controversy, we present the freudian approach, then we review formulations on "becoming woman" by two postfreudians, Klein and Jones, who have not specified femininity through the phallic function, but through the shift from oral libido to the genitals. Last, we present how Lacan interfered in that "phallic quarrel", acknowledging that a woman is inscribed but not wholly in the phallic logic and introducing the notion of a supplementary feminine enjoyment.